2010
DOI: 10.1007/s11695-010-0150-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of A-Line Autoregression Index (AAI) Monitoring on Recovery After Sevoflurane Anesthesia for Bariatric Surgery

Abstract: Monitoring depth of anesthesia may improve anesthetic dosing and postanesthetic recovery in obese patients. Sixty morbidly obese patients undergoing laparoscopic adjustable gastric bandage (LAGB) were randomly assigned to receive anesthesia with sevoflurane titrated by either standard clinical parameters (SCP) (target = baseline hemodynamic parameters ± 20%) or by A-line ARX index (AAI) (target = 20 ± 5). Heart rate, arterial blood pressure, inspiratory and expiratory gas concentrations, and AAI were recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…During induction of anesthesia, together with decrease in AAI, in both groups also heart rate and systemic blood pressure decreased. The observations of Freo et al were similar 27 . During induction of anesthesia, the AAI was always decreased; however other clinical parameters varied.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…During induction of anesthesia, together with decrease in AAI, in both groups also heart rate and systemic blood pressure decreased. The observations of Freo et al were similar 27 . During induction of anesthesia, the AAI was always decreased; however other clinical parameters varied.…”
Section: Discussionmentioning
confidence: 54%
“…AAI was more stable in VOL group. However, lower values of AAI during volatile anesthesia may indicate that volatile anesthetics were overdosed 27 . Intraoperative monitoring of level of anesthesia can reduce the consequences of neurotoxicity of anesthetics 14,15,43,44 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another intervention, possibly promoting increased safety in OSA, is the intraoperative monitoring of anesthesia depth. This has been suggested by Ibraheim et al 172 and Freo et al, 173 who demonstrated that monitoring for titration of levels of inhalational agents reduced the required anesthetic dosage and improved the postanesthetic recovery in patients with obesity.…”
Section: Intraoperative Medication Use In Patients With Osamentioning
confidence: 85%